Penerapan Model Role Play sebagai Upaya Optimalisasi Keterampilan Berbicara di Sekolah Dasar - Rizky, Boby Mahardika Kurnia; Wiratara, Victor Delanu; Sugiarsih, Septia (Journal of Contemporary Issues in Primary Education, 2025)
Speaking skills are one of the important competencies in learning Indonesian in elementary schools. However, the results of observations in class IV A SDN Liwet II show that students' speaking skills are still low due to several internal and external factors. Some internal factors include: Lack of self-confidence, Lack of motivation and interest of students, Use of language structures that tend to be afraid of mistakes, etc. Some external factors, such as: Learning that is still too teacher-centered, Minimal speaking practice during Indonesian language learning, As well as the dominance of the use of regional languages. The research conducted provides a learning solution on the aspect of speaking skills through a role-play learning model based on the animated characters Upin & Ipin which is close and very relevant to the world of children, so it is expected to increase students' interest, confidence, and courage in speaking. This learning is designed interactively and contextually by implementing collaboration from interactions with peers which is expected to make students more active in practicing expressing opinions using good and correct Indonesian. The implementation of this role-play model is expected to be able to optimize students' speaking skills in elementary schools at this time.